(untitled) - Nunen, Anton van (Hoboken, N.J., 2008)
Fiduciary Management offers an in-depth explanation of every facet of this fast-growing approach to organizing the management of an institutional investment portfolio. Expert author Anton van Nunen begins by outlining the historic shift that has brought this strategy to the attention of the investment community and quickly moves on to illustrate fiduciary management in practice; giving advice in terms of asset-liability modeling and financial markets, constructing portfolios, selecting and overseeing investment managers, benchmarking and performance measurement, and reporting
Keywords: Pension trusts,Lương hưu; Management,quản lý